Monitoring Oxidative Status in Winemaking by Untargeted Linear Sweep Voltammetry - Jelena Jeremic; Arianna Ricci; Gabriele Tacconi; Christine Lagarde-Pascal; Giuseppina Paola Parpinello; Andrea Versari (Foods, 2020)
An electrochemical portable device based on linear sweep voltammetry was evaluated for studying the redox behavior of polyphenolic compounds in industrial scale winemaking to infer the effects of selected early processing steps on the vinification trials of Pinot gris, Chardonnay, Vermentino and Sangiovese grapes. For each sample, the redox behavior showed a distinctive voltammetric signal pattern related to the processing step during winemaking, therefore being useful as a potential fingerprint for wine identification and to provide insights about the phenolic content. For instance, there was a high correlation (R2 = 0.72) between the total phenolic compounds (PhenOx) and the easily oxidizable compounds (EasyOx), the latter representing approx. 30% on average of the total phenolics. Furthermore, the maceration of red grapes was concluded after 29 days based on information driven by the phenolics pattern. As expected, during alcoholic fermentation, white wines showed a lower content of phenolic compounds than those found in red wines, with an average ratio PhenOx/EasyOx of about 4.7, 5.0 and 3.6 for Chardonnay, Pinot gris and Vermentino, respectively. The portable tool with miniaturized disposable electrodes showed interesting analytical features that can be exploited for on-site and real-time quality control for monitoring change in phenolic composition during wine processing and storage, and for tailoring winemaking practices to enhance the color stability of products.